Effects of bondline defects on the bond behaviour of CFRP-steel double strap joints - Wu,C; Yu,Y-Z; Tam,L-H; He,L (Composite Structures, 2023)
Adhesive bonding is used frequently for the applications of carbon fiber-reinforced polymer (CFRP) composites in steel structures such as strengthening or joining. However, the bondline defects are inevitable and could negatively affect the bond behaviour between CFRP and steel. Thus, the bondline defects represent a critical hazard and require careful assessment. This paper presents an experimental and numerical study on the effects of bondline defects on the bond behaviour of CFRP-steel double strap joints. The variables include the defect size (up to 35% of the bonded area), number (up to 45) and locations in the bondline. Multiple defects with mixed sizes are considered in a numerical analysis to investigate the effect of the defect number in more detail. It is found that the bondline defects lead to a reduction in the joint capacity. The highest reduction in capacity (36%) is observed when multiple small-sized defects are presented in the bondline. With the increment of the defect area, the failure mode becomes a combination of steel-adhesive interface debonding and CFRP delamination. A design framework is proposed based on the experimental and numerical results for the conservative prediction of the joint capacity with consideration of bondline defects.